Guidance note on documenting qualitative gender equality results. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
The aim of this resource is to assist ADB South Asia Department and partner program and project agencies in collecting and presenting testimonials of select direct beneficiaries of a project gender action plan or gender equality and social inclusion action plan activities. The purpose is to enrich the report on the achievements of the completed gender action plan or gender equality and social inclusion action plan.
Keywords: Gender equality; Asian Development Bank; Electronic book